Faculty Senate, Minutes, February 18, 2010 - Faculty Senate, Valdosta State University (Valdosta, Ga: Valdosta State University Archives and Special Collections, 2010)
Valdosta State University. Faculty Senate, Minutes, February 18, 2010. Chairperson, Patrick J. Schloss; Vice Chairperson, Philip Gunter; Executive Secretary, Barney “Jay” Rickman; Parliamentarian, Vesta Whisler;
1 electronic document. Faculty Senate, Minutes, February 18, 2010. 16 pages.
Keywords: Valdosta State University. Faculty Senate; Minutes (Records); Committees; Electronic records